«La persiana és verda»: idees de correcció i estils intel·lectuals - Viana, Amadeu (Caplletra. Revista Internacional de Filologia, 2000)
Arguments about purity and simplicity are recursive. We gain insight connecting purity in language with correction in other domains. The anthropologist point of view developped by Mary Douglas about «Thought Styles» may help our research in linguistic and pragmatic variation. The main aim of this paper is to show the interest of this programme and the guidelines for its application. Classical thinking about the topic (Cicero, Dante or Locke) could be considered in itsproper terms, aswell as early contributions as that of Jespersen. Conflictive periods of rule conflict (on linguistic norms) could be analysed on these grounds. Discourse analysis and Catalana historiography could renovate their tacit presuppositions if we take into account how values and emotions are socially related to stylistic preferences and pragmatic compromises.